Current Status, Recent Advances, and Main Challenges on Table Olive Fermentation: The Present Meets the Future - Anagnostopoulos, Dimitrios A.; Tsaltas, Dimitrios (Frontiers in Microbiology, 2022)
Table olives are among the most well-known fermented foods, being a vital part of the Mediterranean pyramid diet. They constitute a noteworthy economic factor for the producing countries since both their production and consumption are exponentially increasing year by year, worldwide. Despite its significance, olive’s processing is still craft based, not changed since antiquity, leading to the production of an unstable final product with potential risk concerns, especially related to deterioration. However, based on industrial needs and market demands for reproducible, safe, and healthy products, the modernization of olive fermentation processing is the most important challenge of the current decade. In this sense, the reduction of sodium content and more importantly the use of suitable starter cultures, exhibiting both technological and potential probiotic features, to drive the process may extremely contribute to this need. Prior, to achieve in this effort, the full understanding of table olive microbial ecology during fermentation, including an in-depth determination of microbiota presence and/or dominance and its functionality (genes responsible for metabolite production) that shape the sensorial characteristics of the final product, is a pre-requisite. The advent of meta-omics technology could provide a thorough study of this complex ecosystem, opening in parallel new insights in the field, such as the concept of microbial terroir. Herein, we provide an updated overview in the field of olive fermentation, pointing out some important challenges/perspectives that could be the key to the olive sector’s advancement and modernization.